Changes in smoking status among a longitudinal cohort of gay, bisexual, and other men who have sex with men in Vancouver, Canada. (1st October 2017) - Shariati, Helia; Armstrong, Heather L.; Cui, Zishan; Lachowsky, Nathan J.; Zhu, Julia; Anand, Praney; Roth, Eric A.; Hogg, Robert S.; Oudman, Greg; Tonella, Christina; Moore, David M.
Highlights: 28.8% of human immunodeficiency virus (HIV)-negative and 33.1% of HIV-positive men who have sex with men (MSM) were daily smokers. 62.4% of bisexual men were daily smokers. MSM who made >60, 000 and who were in excellent health were the most likely to quit. MSM with a partner who smokes were less likely to quit and more likely to restart. HIV-positive MSM were more likely to smoke but not more likely to quit. Abstract: Background: Cigarette smoking is common among gay, bisexual, and other men who have sex with men (GBMSM) and most of the mortality gap between HIV-positive and HIV-negative individuals is attributable to smoking. Methods: We recruited sexually active HIV-positive and HIV-negative GBMSM age ≥16 years using respondent-driven sampling. Study visits occurred every six months for up to four years and included a computer-assisted self-interview and clinical assessment. We conducted bivariate analyses to compare factors associated with "never", "former", "daily", or "non-daily" smoking at baseline and longitudinal mixed effects models to examine factors associated with cessation and (re)initiation. Results: 774 participants completed a baseline visit and 525 enrolled in the cohort and completed at least one follow-up visit. At baseline, the median age was 34 years and 31.5% were daily smokers. In follow-up (median = 2.5 years), 116 daily or non-daily smokers (41%) quit at least once and of these, 101 (87%) remained former smokers at their last visit. Smoking cessation was positively associated with incomes ≥60, 000 and self-reported excellent health. Alcohol use, ecstasy use, and having a partner who smokes were associated with decreased odds of cessation. Substance use (cannabis, GHB, and crystal methamphetamine) and having a partner who smokes were positively associated with increasing to/resuming daily smoking. HIV-positive GBMSM were more likely to smoke but not more likely to quit. Conclusions: Targeted, culturally relevant smoking cessation resources are needed, especially for HIV-positive GBMSM. Engaging couples in cessation interventions may be useful.